SOCIAL METAPHORS IN THE INSTALLATION ART OF CONTEMPORARY INDIAN WOMEN ARTISTS - Negi, Neetu; Singh, Gurcharan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Art can be manifested and interpreted by artists to express and transcend changes in their surroundings, as well as showcases tragedies. Art can be used as one of the parameters which broaden our insight towards society. Artists examine social atrocities such as dysfunctional systems, criminal injustices, curbs on the freedom of expression, and childhood traumas which may be embedded in the artists’ minds. Art is the mirror of society and both modernists and post-modernists have tended to demonstrate communal riots and political unrest at the time of global distress. Meanwhile, in the contemporary art world, art is represented with bleak and abject constructions of contemporary subjectivity where, artists basically tend to depict themes such as political issues and reforms, ecological evils, and narratives with social concern. Contemporary paradigms explore new directions to reconnect and be the definition of society in different modes of art. In this study, art and artists will be explored who have contributed to society in profound ways. Their installations will determine the social metaphors evoked and how they unveil the provocative binary of community, how their art has broken stereotypes and became the benefactors of community. This study will also reveal the significance of art in society, in the nation and in the market with visual inputs. In the contemporary domain, art can be shown as personal experiences or with universal themes such as war and migration, which is unfortunately still exists with people suffering irreplaceable scars. This study highlights leading women artists who are critically involved with their societies.